Housing for the "Worst of the Worst" Inmates: Public Support for Supermax Prisons. (June 2013) - Mears, Daniel P.; Mancini, Christina; Beaver, Kevin M.; Gertz, Marc
Despite concerns whether supermaximum security prisons violate human rights or prove effective, these facilities have proliferated in America over the past 25 years. This punishment—aimed at the "worst of the worst" inmates and involving 23-hr-per-day single-cell confinement with few privileges or services—has emerged despite little evidence that the public supports it. Based on public opinion survey data, this study identified the extent to which support exists for supermax prisons and so tested three interrelated hypotheses about variation in public views. The focal contention is that support can be linked to groups that are most concerned with symbolic threats, to those most embracing of a belief in individual agency, and to those who have had negative contacts with offenders. The article concludes with a discussion on implications for theory, research, and policy.